STRATEGI PENINGKATAN PENERAPAN PROTOKOL KESEHATAN DI PASAR PADAYUNGAN TASIKMALAYA - Asep Riyana; Arip Rahman (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
Viruses cannot be destroyed, they can only be weakened. This makes the Indonesian people face new challenges that require them to adapt to new patterns of habits, especially when in public places. The importance of this made the government issue KMK policy No. HK.01.07-MENKES-382-2020 dated 19 June 2020 concerning Adaptation of new habits in public facilities1. Padayungan Market as a traditional market in Tasikmalaya is at risk of the growth of new clusters of virus transmission, in which various transactions and crowds of people occur in buying and selling. The market manager said that efforts had been made through appeals to rapid tests but public compliance with regulations, the manager did not provide guarantees, because regulating behavior in the market was very difficult to do. The results of the research, 55% of traders are not used to implementing the new protocol recommended by the government, they comply with the protocol only when the officers are on the alert, basically traders are afraid of transmitting the virus, but selling cannot be abandoned. Padayungan. With this activity, market traders are more concerned about personal hygiene and the Padayungan market will not become a new cluster of virus transmission.